2016
DOI: 10.1111/jace.14308
|View full text |Cite
|
Sign up to set email alerts
|

High‐Temperature Strength of Boron Suboxide Ceramic Consolidated by Spark Plasma Sintering

Abstract: The spark plasma sintering (SPS) of B6O ceramics using a highly crystalline boron suboxide powder with a low oxygen deficiency level is reported. The monolithic boron suboxide ceramic exhibited a room‐temperature strength of 300 ± 20 MPa, which is comparable to the strength of monolithic boron carbide. With increasing flexural test temperature, the strength of the boron suboxide ceramics increased to 450 MPa at 1400°C. The increase in strength with the temperature is associated with the unique microstructure o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 45 publications
(146 reference statements)
0
2
0
Order By: Relevance
“…In the past, a series of efforts have been devoted to the densification and sintering of B 6 O. Regrettably, due to its low diffusion coefficients and the relatively high vapor pressure at sintering temperatures, full densification of B 6 O is only possible by pressure assisted sintering. The specific method is to heat the B 6 O powder or the mixtures of B and B 2 O 3 powder under a certain pressure to a high temperature of 1700–2200°C for sintering, but even at such a high temperature, the poor sinterability leads to poor fracture toughness (1.7–3.1 MPa m 1/2 ) of the B 6 O ceramics 12–15 . Adding additives is a straightforward approach to improve its sinterability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past, a series of efforts have been devoted to the densification and sintering of B 6 O. Regrettably, due to its low diffusion coefficients and the relatively high vapor pressure at sintering temperatures, full densification of B 6 O is only possible by pressure assisted sintering. The specific method is to heat the B 6 O powder or the mixtures of B and B 2 O 3 powder under a certain pressure to a high temperature of 1700–2200°C for sintering, but even at such a high temperature, the poor sinterability leads to poor fracture toughness (1.7–3.1 MPa m 1/2 ) of the B 6 O ceramics 12–15 . Adding additives is a straightforward approach to improve its sinterability.…”
Section: Introductionmentioning
confidence: 99%
“…The specific method is to heat the B 6 O powder or the mixtures of B and B 2 O 3 powder under a certain pressure to a high temperature of 1700-2200 • C for sintering, but even at such a high temperature, the poor sinterability leads to poor fracture toughness (1.7-3.1 MPa m 1/2 ) of the B 6 O ceramics. [12][13][14][15] Adding additives is a straightforward approach to improve its sinterability. Experiments in the past have confirmed that adding the alkaline earth, 16 rare earth, 17 alkaline oxides, 18 transition metals 19 and their oxides 20 as additives in B 6 O sintering process can effectively reduce the sintering temperature and is conducive to densification.…”
Section: Introductionmentioning
confidence: 99%